Studi Kuantitatif Deskriptif tentang Tingkat Aktivitas Fisik di Kalangan Penghuni Rehabilitasi Narkoba Menggunakan IPAQ - Wiga Nurlatifa Romadhoni; Tri Aji; Haris Kurnianto; Arifin Ika Nugroho (Indonesian Journal of Physical Education and Sport Science, 2026)
Study Purpose. This study aimed to describe the physical activity levels of nine residents at the Rumah Damai Drug Rehabilitation Center in Semarang who participated in a community engagement based structured exercise program. Materials and Methods. A descriptive quantitative design was employed. Physical activity levels were assessed using the International Physical Activity Questionnaire (IPAQ). Data included walking, moderate, and vigorous activities expressed in MET-minutes per week and categorized into low, moderate, and high activity levels. Results. All nine residents (100%) were categorized as having low physical activity levels, with no participants reaching moderate or high categories. The recorded MET-minutes per week were below the recommended threshold for moderate physical activity. These findings indicate that the participants’ overall physical activity levels were limited during the assessment period. Conclusion. The results provide baseline data on the physical activity levels of rehabilitation residents. The findings may inform the development and implementation of structured physical activity programs within rehabilitation settings to support residents’ physical fitness and overall well being.